Probiotic Effector Compounds: Current Knowledge and Future Perspectives - Daliri, Eric Banan-Mwine; Ofosu, Fred Kwame; Xiuqin, Chen; Chelliah, Ramachandran; Oh, Deog-Hwan (Frontiers in Microbiology, 2021)
Understanding the mechanism behind probiotic action will enable a rational selection of probiotics, increase the chances of success in clinical studies and make it easy to substantiate health claims. However, most probiotic studies over the years have rather focused on the effects of probiotics in health and disease whereas little is known about the specific molecules that trigger effects in hosts. This makes it difficult to describe the detailed mechanism by which a given probiotic functions. Probiotics communicate with their hosts through molecular signaling. Meanwhile, since the molecules produced by probiotics under in vitro conditions may differ from those produced in vivo, in vitro mechanistic studies would have to be conducted under conditions that mimic gastrointestinal conditions as much as possible. The ideal situation would however be to carry out well-designed clinical trials in humans (or the target animal) using adequate quantities of the suspected probiotic molecule(s) or adequate quantities of isogenic knock-out or knock-in probiotic mutants. In this review, we discuss our current knowledge about probiotic bacteria and yeast molecules that are involved in molecular signaling with the host. We also discuss the challenges and future perspectives in the search for probiotic effector molecules.